Pengaruh Live Shopping Shop Tokopedia @Npureofficial Terhadap Keputusan Pembelian Produk Skincare - Aghniya Putri Septia H; Yanti Tayo; Tri Widya Budhiharti (KOMVERSAL, 2025)
This research aims to determine the influence of Shop Tokopedia live shopping on purchasing decisions for N'Pure Skincare. The theory used is AIDA (Attention, Interest, Desire, Action) by Elias St. Elmo Lewis. The research method use is a quantitative method with data collection in the form of a questionnaire distributed to followers of the TikTok account @npureofficial with a sample size of 100 respondents. The sampling technique uses non-probability sampling with a purposive sampling method. The data analysis methods used include normality test, simple linear regression test, partial test (t), and coefficient of determination test (R2). The data was tested using IBM SPPS Statistics 30 software. The research results show that Shop Tokopedia live shopping has a significant influence on purchasing decisions for N'Pure skincare products by 61.9% and the remaining 38.1% is influenced by other factors.